Silver Doped Poly(lysine) Polymer Film Modified Electrode for Selective Determination of Norepinephrine - Li, Xia; Yang, Xiaoyang (Asian Journal of Chemistry, 2012)
The silver doped poly(lysine) modified electrode was prepared by cyclic voltammetric method. The modified electrode was shown to possess an excellent selective electrocatalytical effect on the redox of norepinephrine and further used to determine norepinephrine in the presence of uric acid and ascorbic acid in pH 6.0 phosphate buffer solution. The reductive peak current (Ipc) showed a linear relationship with the concentrations (C) of norepinephrine in the range of 1.13 × 10-7-1.13 × 10-4 mol L-1 and a detection limit was 5.66 × 10-8 mol L-1. The modified electrode is high sensitivity, selectivity, stability and has been successfully applied to analyze norepinephrine. The method has high sensitivity, selectivity, stability and practical application of the modified electrode was demonstrated by analyzing injection samples of norepinephrine in the presence of uric acid and ascorbic acid in pH 6.0 phosphate buffer solution.